The Effect of Jump Rope Training Program on the Agility in Deaf Children SLB-B Yayasan Pendidikan Tunas Bangsa (YPTB) Malang City - Pribadi, David Rinekso; Raharjo, Slamet; Andiana, Olivia (Sports Medicine Curiosity Journal, 2023)
Deaf children are those who have lost or suffered from hearing impairment since birth or before the age when their language development is fully formed. One aspect of physical fitness is agility. Through appropriate agility exercises, deaf children can enhance their ability to feel more confident in engaging in physical activities. Jump rope exercises involve coordinated body movements that can help deaf children develop agility, muscle strength, and motor coordination. A pre-experimental approach is used in this quantitative research, and the research design employed is a one-group pretest-posttest. The sample studied consisted of 30 deaf children in grades 3-6 in elementary school. The research indicates that jump rope exercises have a positive impact, leading to an increase in agility in deaf students at SLB-B Yayasan Pendidikan Tunas Bangsa , Malang City. The paired sample t-test results show a significance value of 0.001. The conclusion is that jump rope training has an impact on the agility of deaf students at SLB-B YPTB Malang City, as evidenced by the increase in scores in the post-test.